Analisis Usia Layan Tanah Dasar Pada Struktur Jalan Kereta Api Berdasarkan Perbedaan Ketebalan Balas (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2023)
Railway track is important component in the operational of railway. Railway track structre consist of layers of ballast, sub-ballast, and subgrade. Subgrade located at the bottom of railway track structure thus make this layer hold the whole structure above. In case of damage to the subgrade, then there will be a lot of mismatches in the structure of the overlying layers and reduced stability of the railway track structure. One way to prevent damage on the subgrade is by doing maintenance berfore reaching its service life. This research aims to find out the effect of ballast thickness to subgrade service life. The Analysis was performed numerically using ANSYS 2023 software to determine vertical compressive stress used in the service life calculation. At a ballast thickness of 200 mm the subgrade service life is 43.7 years. Based on PM 60/2012, the minimum ballast thickness is 300 mm. At this thickness, the subgrade service life is 62.7 year, while at the ballast thickness of 500 mm the subgrade service life is up to 98.99 years.